Standing Type in Dicey/Marshall Issues of The Berkshire Tragedy. (12th June 2020) - Atkinson, David
Abstract: This article considers six printings of the same ballad, The Berkshire Tragedy, by the same bookseller/printer, the Dicey/Marshall firm, which was the major producer of ballads in London throughout the mid-eighteenth-century. The results are rather startling and demonstrate that the ballad was kept in standing type through five different issues, in spite of a change from four-column to five-column format. These findings add to our knowledge of ballad production in the eighteenth century, and call into question the idea of ballads as ephemera.